A CRITICAL REVIEW TO SOFTWARE RELIABILITY ASSESSMENT - Sangeeta, Sitender (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
Reliability of the software is an important issue in day today life as human life is heavily dependent on the software and software controlled applications. Ensuring the reliability of this software is not an easy task. A lot of research has been done in the last decades for software reliability assessment. The new models are being developed by the researchers which are directly or indirectly related with the already developed models. These new models are having their origin from the most basic models. In this paper, a critical review has been done that involves the most basic models and the models evolved from existing models. The survey here shows how the new models have been developed from the already developed models. This review will provide a new way for the researchers in order to develop new model that can estimate the reliability of the software more accurately.